Red blood cell folate as a risk factor for breast cancer among patients at a tertiary hospital in Uganda: a case control study - Rukundo, Gideon; Galukande, Moses; Ongom, Peter; Fualal, Jane O. (World journal of surgical oncology, 2014)
Folate has been shown to play a complex but unclear role in carcinogenesis, with some studies showing that low folate intake protects against early carcinogenesis while high folate intake promotes advanced carcinogenesis. Other studies have shown that high folate is associated with decreased breast cancer risk and overall survival, yet others found no such association. This study therefore sought to determine the association between red blood folate levels and breast cancer among women seen at a tertiary Ugandan hospital. Methods: A case control study was conducted where female patients with a histological diagnosis of breast cancer were recruited as cases, and females without cancer attending other surgical clinics as controls. Demographics and social behavior data were collected and 5mls of blood drawn for laboratory testing of red blood cell (RBC) folate, serum vitamin B12 and RBC count. Ethical approval was obtained. Results: In this study, a total of 145 women were recruited as 72 cases and 73 controls. The odds of having breast cancer among women with normal folate levels compared to those with low folate levels were 1.4 (95% CI 0.7 to 2.9) P = 0.290. Ninety participants (63%) had low RBC folate and 53 participants (37%) had normal RBC folate. Thirty five (45%) of the women from a rural setting had normal folate levels compared to 18(28%) women from an urban setting.
Keywords: Red blood cell; Folate; Breast cancer